Comparison of Assessment of Abbreviated Burn Severity Index (Absi) and Belgian Outcome of Burn Injury (BOBI) at H. Adam Malik General Hospital (Sumatera Medical Journal, 2022)
Background: Assessment of length of stay and mortality in patients with burn injuries is essential to support clinicians in making clinical decisions. In Indonesia, there are several scoring systems used by hospital centers to assess the mortality of burn patients, such as the Belgian Outcome of Burn Injury (BOBI) and the Abbreviated Burn Severity Index (ABSI). However, different results were obtained in studies that examined the comparison of the results of the scoring system.Method: The type of research used in this research is unpaired comparative analysis research using a cross-sectional design. The data to be used is secondary data taken from medical records.Results: Respondents with death status were found in the serious, severe, and maximum ABSI categories, p=0.001 (p